[Papers] (UNESCO ParisFR, 1983)
Examines the situation of and priorities for the development of education in the 3 least developed countries and provides a statistical analysis of international cooperation in education in these countries. The final report identifies needs and priorities in regard to education and highlights problems such as the eradication of illiteracy, formal and non-formal education, the role of secondary and higher education and education in relation to rural development.
DC